Rapid Verbal Persuasion to increase influenza vaccine uptake: protocol for a randomized hybrid type 2 effectiveness -implementation trial - Siyuan Liu; Lan Gao; Yingying Jin; Jiangyun Chen; Dadong Wu; Yiyuan Cai; Tao Wang; Sanhao Huang; Ciling Yan; Run Wang; Dong Roman Xu (BMC Health Services Research)
Abstract Background While influenza vaccines are the most effective measure for preventing influenza, uptake rates in China remain relatively low. Rapid Verbal Persuasion (RVP), with highly rapid fashion, has a strong evidence base in promoting behavior change. Despite this, it is underused or rarely evaluated in the context of vaccination. Additionally, the success of RVP implementation in vaccination clinics hinges on the motivation of vaccination staff, which remains critical even with stable contextual factors. Multifaceted incentive-based implementation strategies, which aim to enhance motivation to promote the implementation of evidence-based practices, could be advantageous. This study protocol outlines an implementation-effectiveness hybrid type 2 design to evaluate the effectiveness of both the incentive-based implementation strategies on implementation outcomes and RVP on increasing influenza vaccination rates. Method This study will be conducted as a two-tiered cluster of randomized controlled trials over three months. Initially, 32 vaccination clinics will be randomly allocated to one of two study arms: (a) implementation of RVP or (b) no implementation. At the end of the study period, differences in influenza vaccination status between the intervention and control groups will be compared (primary outcome). Subsequently, a cluster randomized factorial trial will be conducted, involving 16 clinics implementing RVP. This trial will aim to compare the impact of various implementation strategies (different combinations of incentives) on fidelity in RVP implementation (primary outcome). Data collection for the primary outcomes will include unannounced exit interviews. Modified Poisson regression models and generalized linear mixed-effects models will be utilized to analyze the association between primary outcomes and interventions. Conclusion The study aims to enhance the influenza vaccination rate in China by developing financial and non-financial incentives that allow vaccination staff to deliver RVP with greater motivation. Furthermore, the evidence generated from this multi-center trial will assist policymakers in improving current incentive systems within immunization services. Trial registration Chinese Clinical Trial Registry. Trial identifier: ChiCTR2400091302 (Registration Date: October 25, 2024); ChiCTR2400091324 (Registration Date: October 25, 2024).